Focused Conversation As A Data Gathering Procedure In Qualitative Research: A Systematic Review Of The Use Of ORID And DEAL Models In Education, Psychology, And Organizational Studies - C. Lunar, Bernardo; Dimaculangan, Irish A. (Journal of Neonatal Surgery, 2025)
Focused conversation methods, particularly those framed through the ORID (Objective, Reflective, Interpretive, Decisional) and DEAL (Describe, Examine, Articulate Learning) models, have gained traction as structured but flexible approaches to qualitative data collection. This systematic review examines 60 empirical studies from 2010 to 2024 that adopted focused conversations informed by either or both models within educational, psychological, and organizational research. Using a PRISMA-informed protocol for qualitative synthesis, the review analyzes patterns in design, facilitation, data richness, and analytic translation. Findings indicate that ORID was primarily used to guide thematic depth in reflective dialogue, while DEAL emphasized learning outcomes and critical engagement. In education, both models enhanced student and teacher reflection; in psychology, they facilitated narrative and emotional articulation; and in organizations, they supported structured team sense-making. Despite their benefits, issues with fidelity to each model's sequence and insufficient documentation of facilitators’ positionality were noted. Implications include a call for methodological refinement, cross-model integration, and clearer analytic mapping strategies in future qualitative inquiries